Assessing the Loyalty of Shoppers of Attire Multi - Brand Outlets : A Research Study - Rupesh Kumar, M.; Narayanan, A. G. V. (Indian Journal of Marketing, 2017)
This study aimed to ascertain whether the loyal shoppers referred their loved ones, friends, relatives, peer groups, well wishers, etc. to their preferred MBOs for fulfilling their shopping requirements. The study was conducted with 400 respondents at Coimbatore city, India. The research is a descriptive one. The data was collected using the mall intercept survey method. The data was analyzed using frequency distribution, cross tabulation, reliability and validity test, chi-square test, correlation, and t - test. Majority of the respondents sustained with the same MBOs due to various reasons like wider designs, collections, and product quality. The study revealed that the shoppers of MBOs were loyal towards their stores because 38% of the respondents referred five to ten people and 38.5% brought two to four new customers to shop from their preferred MBOs. The above facts like customer referrals and frequent purchases were the components chosen for this study, which proved the loyalty of shoppers towards the multi-brand outlets.